Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1989
DOI: 10.1148/radiology.170.3.2916025
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Gd-DTPA-enhanced MR imaging of the kidney: experimental results.

Abstract: To determine the normal appearance of dynamic enhanced renal magnetic resonance (MR) images, 25 rabbits were injected with Gd-DTPA and 32 consecutive gradient-recalled images were acquired. Several rabbits were also imaged in dehydrated (five animals) and overhydrated (seven animals) states. A reproducible renal enhancement pattern is observed that can be divided into three phases. During the first phase, a peripheral dark band appears, probably representing arrival of Gd-DTPA within the arterioles and vasa re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
55
0

Year Published

1996
1996
2013
2013

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 121 publications
(57 citation statements)
references
References 0 publications
1
55
0
Order By: Relevance
“…This phenomenon has been described in previous studies using GRE sequences. Choyke et al (14) found a lower MR signal when they measured Gd-DTPA concentrations above 12 mmol Gd-DTPA per liter using a GRE sequence with a flip angles of both 40°and 90°. Testing the MR sequence used in the present study, we found proportionality between the MR signal and Gd-DTPA concentration up to approximately 10 -20 mmol Gd-DTPA per liter (1).…”
Section: Discussionmentioning
confidence: 99%
“…This phenomenon has been described in previous studies using GRE sequences. Choyke et al (14) found a lower MR signal when they measured Gd-DTPA concentrations above 12 mmol Gd-DTPA per liter using a GRE sequence with a flip angles of both 40°and 90°. Testing the MR sequence used in the present study, we found proportionality between the MR signal and Gd-DTPA concentration up to approximately 10 -20 mmol Gd-DTPA per liter (1).…”
Section: Discussionmentioning
confidence: 99%
“…Functional MRI of the kidneys began as a field with the introduction of gadolinium-DTPA (Gd-DTPA) also known as gadopentatate dimeglumine in the 1980s [4, 5]. It was quickly realized that, as a small molecule <1 kDa, Gd-DTPA was filtered at the glomerulus and neither secreted nor reabsorbed in the tubules.…”
Section: Introductionmentioning
confidence: 99%
“…Before the injection of gadopentetate dimeglumine, little intracortical contrast enhancement was observed in the renal cortex, except for the blood vessels, which appeared as bright spots on the zoomed-in image in Figure 3, C1. Twenty minutes after injection of a low-dose bolus of gadopentetate dimeglumine at 5 mmol/kg, bright strips appeared on the image in Figure 3, D1, as gadopentetate dimeglumine was filtered out of blood and became sufficiently concentrated inside renal tubules (19). This contrast enhancement persisted for the entire imaging session, possibly due to slow excretion of gadopentetate dimeglumine for a rat under deep anesthesia.…”
Section: Technical Developments: Wireless Amplified Nuclear Mr Detectmentioning
confidence: 97%
“…All contrast agents were administered through tail veins. Dilute gadopentetate dimeglumine concentrates in the renal tubules during the urine formation (19) and increases the signal intensity of the image, whereas cationized ferritin binds specifically to the basement membrane of glomeruli (20) and reduces the image intensity. To quantitatively identify contrast-enhanced regions, the intensity value of each pixel was compared with the local average and their difference was divided by the noise floor to obtain the deviation-to-noise ratio (DNR).…”
Section: Technical Developments: Wireless Amplified Nuclear Mr Detectmentioning
confidence: 99%